Factor Analysis with Health Belief Model on the Adherence to Methadone Maintenance Therapy - Seindy Arya Kusuma Timoer; Bhisma Murti; RB Soemanto (Journal of Epidemiology and Public Health, 2016)
Background: Methadone maintenance therapy is one of substitution therapy is needed as a harm reduction approach of transmission of HIV / AIDS through injecting drugs. To achieve the success of the therapy, therapy adherence is very important. This study was aimed todetermine the factors affecting adherence methadone maintenance therapy using the approach of the Health Belief Model in clinical methadone maintenance therapyprograms.Subject and Methods: This was an analytical observation study with qualitative method, conducted in a community health center PTRMManahan Surakarta. A total ofsample was selected with snowball. Thedata collected by using in-depth interviews, observation and document. The validityincluded triangulation of sources, methods, theory and research. The data analysis was using analytical models mating patterns, reduction, data presentation and analysis of data that form a pattern that can reveal the Health Believe Model or HBM linkage with therapy adherence.Results: The results showed the factors of patients using the drug include family background, social environment, and knowledge. Factors underlying patients adhere to therapy, among others, those included in the high risk group of HIV / AIDS; the seriousness of the disease of HIV / AIDS; improved quality of life, side effects of methadone are more severe than injecting drug use; family and NGOs as a driving force to follow programswhich is an instrument of HBM. Programs patient factors for non-compliant in following methadone maintenance therapy include patients still using drugs, objected to the levy on programs, and saturated with duration of therapy.Conclusion: Methadone maintenance therapy adherence factors include the perception of vulnerability, perceived seriousness, benefits, barriers and trigger actions. Areas of compliance include methadone maintenance therapy patients were still using drugs, objected to the levy on programs, and saturated with duration of therapy.Keywords: injecting drug users, HIV / AIDS, reduction, HBM, compliance therapy, methadone maintenance therapyCorrrespondence: Seindy Arya Kusuma Timoer.  Masters Program in Public Health, Sebelas Maret University, SurakartaJournal of Epidemiology and Public Health (2016), 1(1): 49-57https://doi.org/10.26911/jepublichealth.2016.01.01.06